A hybrid plasma de-icing actuator by using SiC hydrophobic coating-based quartz glass as barrier dielectric. (1st July 2021) - Zheng, Xing; Song, Huimin; Bian, Dongliang; Liang, Hua; Zong, Haohua; Huang, Zhengyong; Wang, Yaogong; Xu, Wenjie
Abstract: Aircraft icing poses a major threat to flight safety, and plasma anti-/de-icing becomes a new approach in the field of anti-/de-icing in recent years. In this paper, a surface dielectric barrier discharge (SDBD) plasma actuator with SiC hydrophobic coating-based quartz glass is designed and fabricated. Actuated by nanosecond high voltage pulse, its de-icing characteristics are explored experimentally and compared with the uncoated actuator. The results show that under the same actuation parameters, the discharge current peaks and the power consumption of SDBD are reduced with hydrophobic coating, which can be further verified by surface temperature distribution. Intensified CCD camera images indicate that after the adding of SiC coating, the discharge propagation process of SDBD does not change significantly. For both coated/uncoated actuators, two discharges occur during the voltage rise and fall phases respectively, while no discharge occurs during the pulse width phase, but the coated actuator exhibits slightly longer plasma dissipation time. Static de-icing results reveal that the instantaneous energy utilization rate of the coated actuator at 60 s of de-icing process is about 54% higher than that of the uncoated actuator, which can be explained by two aspects: one is to weaken the adverse effects of melted water on the discharge plasma to a maximum extent, and the other is to reduce the contact area between the ice accretion and the hydrophobic surface.